O funkcji perswazyjnej tekstów marketingowych umieszczanych na etykietach piw .......... 463 - Mazur, Rafał; Żebrowska-Mazur, Barbara (Gwara i kultura w słowie zapisane: Księga jubileuszowa dedykowana Profesorowi Józefowi Kąsiowi, 2025)
ON THE PERSUASIVE FUNCTION OF MARKETING TEXTS PLACED ON BEER LABELSThe paper analyzes the persuasive mechanisms utilized in marketing texts found on labels and back labels of beer bottles. These texts might take the form of a brief description focused on highlighting the characteristics of the beer – its style, flavour profile, or ingredients used in the brewing process. Sometimes, however, manufacturers shape these messages as short stories about the advertized product. By introducing specific characters, places, and symbols, they appeal to both the senses and the emotions of the consumer. Beyond merely conveying information about the drink, these narratives also build an atmosphere intended to accompany the drinking experience. The use of both of these strategies showcases the remarkable creativity of beer producers who enliven their texts with numerous humorous elements, puns, and cultural references. Creativity of this kind is generally well-received by consumers who approach beer tasting not only as a sensory experience but also as an intellectual one. This is connected with a shift in the stereotype of beer as merely an alcoholic beverage.